Video-based microlearning and the impact on programming skills and technology acceptance - ALshammari , Fehaid Lafi (Journal of Education and e-Learning Research, 2024)
Microlearning is a modern learning modality that has been adopted in recent years for student education. This study aimed to reveal the effect of video-based microlearning on the development of programming skills and technology acceptance among intermediate school students. The study used a quasi-experimental design for two groups. A technology acceptance scale and a performance observation card for programming skills were prepared in order to collect data for the study. A cluster random sample of intermediate school students participated in video-based micro learning. The students were divided into two groups: the experimental group (consisting of 31 students) and the control group (consisting of 32 students). The results of the study showed that there were statistically significant differences between the mean scores of both study groups in favor of the experimental group in the post-application of the performance observation card for programming skills. However, there were statistically significant differences between the mean scores of the students in the experimental group in the pre- and post-application of the technology acceptance scale in favor of the post application. The study suggested that computer teachers might benefit from employing video-based microlearning to teach students programming skills at different stages based on these results. Suggestions related to the research findings are also provided.